125th Anniversary Review: The science of the tropical cereals sorghum, maize and rice in relation to lager beer brewing. Issue 1 (17th June 2013) - Taylor, John R. N.; Dlamini, Bhekisisa C.; Kruger, Johanita
Abstract : Mainstream lager beer brewing using the tropical cereals sorghum, maize and rice, either as malt or as raw grain plus commercial enzymes, is becoming widespread. This review examines the differences in composition between these tropical cereals and barley and their impact on brewing processes and beer quality. All of these cereals have a starch gelatinization temperature some 10 °C higher than barley. The sorghum prolamin proteins are particularly resistant to proteolysis owing to disulphide cross‐linking involving γ ‐kafirin. Unlike barley, the major endosperm cell wall components in sorghum and maize are arabinoxylans, which persist during malting. The rice cell walls also seem to contain pectic substances. Notably, certain sorghum varieties, the tannin‐type sorghums, contain considerable levels of condensed tannins (proanthocyanidins), which can substantially inhibit amylases, and probably also other brewing enzymes. Tropical cereal malts exhibit a similar complement of enzymic activities to barley malt, with the notable exception of β ‐amylase, which is much lower and essentially is absent in their raw grain. Concerning beer flavour, it is probable that condensed tannins, where present in sorghum, could contribute to bitterness and astringency. The compound 2‐acetyl‐1‐pyrroline, responsible for the popcorn aroma of maize and also the major aroma compound in rice, presumably affects beer flavour. However, much more research is needed into tropical cereals and beer flavour. Other future directions should include improving hydrolysis of prolamins into free amino nitrogen, possibly using prolyl carboxypeptidases and investigating tropical cereal lines with useful novel traits such as high amylopectin, high protein digestibility and low phytate. Copyright © 2013 The Institute of Brewing & Distilling